Long term analysis of high-resolution E-region neutral wind estimations over Jicamarca: First results - Flores, Roberto (2024)
Ground based techniques can be used to measure neutral zonal winds, such as the ISR technique which is usually performed to estimate zonal wind profiles from measured ion drifts at mid- and high-latitude but cannot be used at low-latitudes due to clutter from coherent echoes at E-layer (EEJ). Additionally, the Spread Spectrum Interferometric Multistatic meteor radar Observing Network (SIMONe) system, deployed in September 2019, can estimate neutral winds from specular meteor trail echoes in the mesosphere and lower thermosphere (MLT) region (70 - 110 km) which includes the EEJ layer, however the time resolution is 1 hour and it probes a larger volume than our oblique radar, then estimated winds will be a result of a contribution from different regions. Space-based missions have also been used to measure these winds such as the Michelson Interferometer for Global High-Resolution Thermospheric Imaging (MIGHTI) on board the ICON satellite, the Wind Imaging Interferometer (WINDII) on the Upper Atmosphere Research Satellite (UARS) among others, but their measurements are not continuous over a specific latitude and longitude as they orbit around the planet. On the other hand, a technique to estimate zonal neutral winds from oblique EEJ type II Doppler shifts, sampled every minute approximately, was proposed by Shume et al. [2005]. This method predicts Doppler shifts from neutral winds, compares the Doppler with the measured ones and updates the winds until the best data-model agreement of the Doppler shift (RMSE≤2.0). Although wind estimations are limited to the EEJ echoes detection and SNR intensity, this method provides high time resolution wind profiles from 97 to 107 km approximately and might be complemented by other techniques. This work presents the first results of neutral wind estimations over the Jicamarca Radio Observatory (JRO), a facility of Instituto Geofísico del Perú (IGP), at the EEJ region with a resolution of 5 minutes and 700 meters using oblique spectra data fitted by a skewed Gaussian distribution.